The Judicial Construction of Economic, Social and Cultural Rights in the Case of the Constitutional Court of Colombia (2009)
The paper argues that the Constitutional Court of Colombia has understood economic, social and cultural rights (ESCR) from the perspective of a traditional theory of rights according to which they are achievements that cannot be overridden by conflicting public interests. As a result, the Court has favored a categorical formula of adjudication according to which judicial activity focuses on the definition of the scope of the right. Competing public interests may be taken into account in order to establish the scope of the right, but once that scope is defined, it cannot be overridden by conflicting public interests. Therefore, the conception of ESCR that the Court of Colombia has adopted differs from the South African conception. The South African Constitutional Court regards ESCR as protective shields against conflicting governmental interests. This theory allows for positions of rights to be balanced against countervailing governmental interests. Given the tensions that these theories of rights and formulas of adjudication create in terms of judicial discretion and democratic debate, some intermediate formulas have been proposed. In the final part of the paper, these proposals are analyzed and some suggestions are made that contribute to the debate.